2022
DOI: 10.1007/s13555-022-00814-x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Cervical Muscle Tension Improves Psychological Stress and Symptoms of Moderate-to-Severe Atopic Dermatitis: a Case Series with 20 Patients

Abstract: Introduction: Atopic dermatitis (AD) is a chronic relapsing inflammatory skin disease that is triggered by intense pruritus, impaired skin barrier function, and immune responses to allergenic substances. Break-through therapies for AD include molecular-targeted drugs and the effective management of severe symptoms of AD. However, patients with clinical improvements may continue scratching owing to the influence of psychological stress, which might lead to quick relapses of stressors and subsequent intensive sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Bae, et al found that PMR intervention consisting of physical and mental components for 4 weeks significantly reduced anxiety and depression. Several other case series, both in adults and pediatrics, have shown similar results 30 , 88 .…”
Section: Discussionsupporting
confidence: 60%
“…Bae, et al found that PMR intervention consisting of physical and mental components for 4 weeks significantly reduced anxiety and depression. Several other case series, both in adults and pediatrics, have shown similar results 30 , 88 .…”
Section: Discussionsupporting
confidence: 60%
“…A recent RCT conducted in Germany revealed potential beneficial changes to patient-reported baseline itching intensity, disease severity, and disease-associated quality of life after undergoing hypnotherapy and treatment with an intermittent fasting program [39]. Another case series studying the use of an osteopathic manipulative treatment to relieve cervical muscle tension in 20 patients with moderateto-severe AD on no other medicated topical or systemic treatments demonstrated overall improvement in the visual analog scale score for pruritus, and the total hospital anxiety and depression score was also notably reduced [40]. Addressing the psychological impact of AD as adjunctive disease treatment has shown benefit in multiple clinical trials and should be included as a method in multimodal disease management [38][39][40].…”
Section: Therapeutic Approachesmentioning
confidence: 99%